MANTENIMIENTO PREVENTIVO Y CORRECTIVO GENERAL DE UN AVEO EMOTION DOHC 1.6 - ZUMBA VASQUEZ, JUAN GERARDO (2015)
The preparation of this document is to demonstrate the importance and benefits of performing preventive maintenance on the vehicle mileage according to their work, trying to reduce or avoid possible the application of corrective maintenance because this has considerable disadvantages in terms of price and time. It may be noted that to carry out the development and implementation of the project described was proceeded to the respective overall assessment of the vehicle in the mechanical and electrical as well as the indications and procedures for the respective unarmed, erection, assembly, disassembly and adjustment described by the shop manual for different jobs in vehicle systems. Also is trying to raise awareness to the owner of the vehicle in selecting appropriate fluids and lubricants specified by the dealer's manual as well as the importance of automotive maintenance in order to preserve and extend the lifespan of it, but mostly consider the importance of having a vehicle in good condition for his personal safety of your passengers and other people in the environment surrounding it.